On the choice of appropriate development strategy: Insights from CGE modelling of the Mozambican economy - Henning Tarp Jensen; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper makes use of a 1997 computable general equilibrium (CGE) model to analyse three potential strategies that Mozambique can pursue unilaterally with a view to initiating a sustainable development process. They include (i) an agriculture-first strategy, (ii) an agricultural-development led industrialization (ADLI) strategy, and (iii) a primary-sector export-oriented strategy. The ADLI strategy dominates the other development strategies since important synergy effects in aggregate welfare arise from including key agro-industry sectors into the agriculture-first development strategy. Moreover, the ADLI strategy can be designed so it has a relatively strong impact on the welfare of the poorest poverty-stricken households, and still maintain the politically sensitive factorial distribution of income.
Keywords: D58; O11; 330; CGE modelling; development strategy; Mozambique; Entwicklungsstrategie; Allgemeines Gleichgewicht; Mosambik